HAJAT HIDUP ORANG BANYAK: JALAN KETIGA ILMU PEMERINTAHAN - Fernandes Simangunsong; Guno Tri Tjahjoko (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
the emergence of the third way of thinking was motivated by the formation of government science in Indonesia which was influenced by 2 (two) schools, namely Continental Europe, which brought the term "authority" to Indonesia, and "Anglo Saxon" who introduced the concept of "power" (power). Both streams color the teaching of government science in Indonesia, this has an impact on government science being perceived as "public policy", "bureaucracy" or "politics". The implication of the application of these two schools is that they marginalize the focus of government science from people's sovereignty in accordance with the mandate of the 1945 Constitution.